Calculation of light backscattering matrix by the DDA method for arbitrary particles of cirrus clouds for lidar remote sensing - Konoshonkin, Alexander V.; Shishko, Viсtor A.; Salnikov, Kirill S.; Timofeev, Dmitriy N.; Kustova, Natalia V.; Borovoi, Anatoli G. (Proceedings of SPIE)
The paper presents a solution to the problem of light scattering by small randomly oriented ice crystals of arbitrary shape. The solution was obtained within the discrete dipole approximation. The particle sizes ranged from 0.02 up to 4 µm. The wavelength of the incident radiation is 0.532 µm, the refractive index is 1.3116. The influence of the number of dipoles per lambda and number of orientations on the convergence of the solution is shown. It is shown that the computation time has an exponential law dependence on particle size.